A new electrophoretic focusing principle: focusing of nonamphoteric weak ionogenic analytes using inverse electromigration dispersion profiles - Gebauer, Petr; Malá, Zdena; Bocek, Petr (Electrophoresis, 2010)
This contribution introduces a new separation principle in CE which offers focusing of weak nonamphoteric ionogenic species and their inherent transport to the detector. The prerequisite condition for application of this principle is the existence of an inverse electromigration dispersion profile, i.e. a profile where pH is decreasing toward the anode or cathode for focusing of anionic or cationic weak analytes, respectively. The theory presented defines the principal conditions under which an analyte is focused on a profile of this type. Since electromigration dispersion profiles are migrating ones, the new principle offers inherent transport of focused analytes into the detection cell. The focusing principle described utilizes a mechanism different from both CZE (where separation is based on the difference in mobilities) and IEF (where separation is based on difference in pI), and hence, offers another separation dimension in CE. The new principle and its theory presented here are supplemented by convincing experiments as their proof.
Keywords: elektroforéza kapilární; chemické modely; Computer Simulation; Spectrophotometry, Ultraviolet; spektrofotometrie ultrafialová; počítačová simulace; Acids; Models, Chemical; koncentrace vodíkových iontů; ionty; Ions; kyseliny; Hydrogen-Ion Concentration; Electrophoresis, Capillary